The effects of human behavior on the efficiency of routing policies in order picking: The case of route deviations. (September 2017) - Elbert, Ralf M.; Franzke, Torsten; Glock, Christoph H.; Grosse, Eric H.
Highlights: An exploratory case study is used to highlight how order pickers perceive order picking routes. A simulation model is developed to quantify the effects of route deviations on routing policies. Optimal routing policy keeps its performance advantage even when routing deviations occur. Abstract: Retrieving items from storage locations in warehouses, commonly referred to as order picking, is often performed by human workers. The high amount of human work involved in order picking turns this activity into a time- and cost-intensive process step in warehouse operations. Due to the cost impact of manual order picking, researchers have developed various planning methods that support practitioners in realizing an efficient order picking process. Among these planning approaches, methods that support the routing of order pickers through the warehouse have been a very popular research topic in recent years, with the focus being both on the development of optimal and heuristic routing policies. Surprisingly, problems that may arise when implementing picker routes for human workers in practice have not been investigated so far. There is, however, empirical evidence that order pickers tend to deviate from optimal routes, putting the efficiency of these routing approaches at stake. This paper presents a detailed evaluation of the relative efficiency of order picker routing policies when order pickers deviate from pre-specified routes. First, different behavioral factors that may result in deviations from pre-specified routes are identified in a state-of-the-art literature review and using the results of an exploratory case study. Subsequently, an agent-based simulation model is developed to quantify the effects of deviations from pre-specified routes. The simulation model is then used to compare different routing policies in an extensive simulation experiment. The results of this paper indicate that even in case order pickers deviate from given routes, implementing the optimal routing policy should be the preferred option in most real-world scenarios.